Mary Anne's bad-luck mystery - Martin, Ann M., 1955-; Cheng, Cynthia Yuan (Baby-sitters Club (Graphix (Firm)), 2023)
Ever since Mary Anne threw away a chain letter she got in the mail, the Baby-sitters Club has been having the worst luck. As Halloween approaches, Mary Anne worries something truly terrible is going to happen. So when she receives another note in the mail with instructions to wear a bad-luck charm, she quickly decides to comply before things get worse.